Assessment of physicochemical parameters, and antioxidant properties of mango concentrate during different storage intervals - Muhammad Samiullah Awan; Asif Ahmad; Waseem Khalid; Muhammad Zubair Khalid; Ionica Coţovanu; Farhan Afzal; Suliman Yousef Alomar; Shazia Yaqub; Manal Hadi Ghaffoori Kanaan; Sura Saad Abdullah; Felix Kwashie Madilo (International Journal of Food Properties)
Pakistan is one of the biggest mango producing country in the world. Post-harvest losses of mango occur due to lack of storage facilities. Mango can be converted into concentrate to utilize it for longer period. In the current study, the physicochemical profile and storage stability of mango concentrate was investigated to evidence the opportunity of preservation method. Three different concentrations (0.1%, 0.2%, and 0.5%) of citric acid, sodium benzoate and potassium sorbate were applied. All chemical preservatives significantly (p ˂ 0.05) increased viscosity, total soluble solids (TS), reducing sugar (RS), non-reducing sugar (NRS), total soluble solids (TSS), and titratable acidity (TA), while the moisture content, pH, DPPH antioxidant activity, TPC (total phenolic content), TFC (total flavonoid content) and the level of texture acceptance decreased during the storage. The moisture content was decreased from 43.4% to 34.9% during storage. Phytochemical analysis showed that mango concentrate is a potential source of antioxidant compounds and has higher DPPH radical scavenging activity. Regarding preservation solution, it is suggested that sodium benzoate and citric acid might be utilized for industrial applications.